2016
DOI: 10.1039/c5ra27099e
|View full text |Cite
|
Sign up to set email alerts
|

Improved electrochromic performance of a radio frequency magnetron sputtered NiO thin film with high optical switching speed

Abstract: A nickel oxide (NiO) thin film with better reversibility, high optical modulation, and enhanced coloration efficiency with fast switching time was prepared using radio frequency (rf) magnetron sputtering technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 64 publications
2
28
1
Order By: Relevance
“…The shifting of their band position leads to the small variations observed in the crystallinity of the sputtered NiO thin films. First order LO mode and second order 2LO modes are associated with the vibration of Ni-O bonds and also the sharp intense band around 554.18 to 560.37 cm −1 indicates the existence of Nickel defects or Ni +3 ions exist along with the Ni +2 ions which were also confirmed by the XPS characterization [11]. Figure 7 depicts AFM images of the NiO thin films performed in tapping mode with scan area~2 μm×2 μm.…”
Section: Chemical Analysismentioning
confidence: 59%
See 2 more Smart Citations
“…The shifting of their band position leads to the small variations observed in the crystallinity of the sputtered NiO thin films. First order LO mode and second order 2LO modes are associated with the vibration of Ni-O bonds and also the sharp intense band around 554.18 to 560.37 cm −1 indicates the existence of Nickel defects or Ni +3 ions exist along with the Ni +2 ions which were also confirmed by the XPS characterization [11]. Figure 7 depicts AFM images of the NiO thin films performed in tapping mode with scan area~2 μm×2 μm.…”
Section: Chemical Analysismentioning
confidence: 59%
“…The characteristic core level O1s peak located at 529.16 to 529.27 eV is ascribed to Ni +2 because of lattice oxygen interaction in the form of Ni-O octahedral bonding of NiO [37]. The peak at 530.83 to 531 eV represent the Ni +3 which indicate vacancy or metal deficiency in the films and a small peak located at ∼531.90 to 532.10 eV represents the O-H group and 533.26 eV represents the adsorbed O 2 element present in the deposited NiO surface layer [11,38]. The oxidation state of Ni +2 peak position is slightly shifted from 529.16 to 529.27 eV with increase in the oxygen partial pressure from 5 to 10 sccm during the deposition.…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The plot clearly showed that there were three processes involved due to free movement of H + ions inside the three‐electrode system. First was the semi‐circular curve obtained at the high frequency region correspond to the migration of the H + ions at the working electrode‐electrolyte interface, second was the middle frequency range of the plot correspond to the charge‐transfer process which gave the value of resistance of charge‐transfer, and third was the inclined straight line at the low‐frequency region correspond to Warburg diffusion . Bode plot exhibited change in phase angles and resistance with log frequency was shown in Figure B.…”
Section: Resultsmentioning
confidence: 99%
“…There are many known methods for the NiO/Ni(OH) 2 film deposition: magnetron sputtering [11], vacuum deposition [12], chemical bath deposition [13], sol-gel [14], pulse laser deposition [15], spray pyrolysis [16] and electrochemical deposition [17].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%